Conclusions and future perspectives - Panuwan Chantawannakul (2018)
© Springer Nature Singapore Pte Ltd. 2018. All rights reserved. In this chapter, we briefly provide future directions for study that we believe will broadly benefit the bees and people of Asia and abroad. Asia maintains the highest biodiversity of native honey bee species on the planet, in addition to the introduced European honey bee. This intermingling of species has promoted a number of virus-host shifts that potentially threaten honey bees because of a lack of coevolution. This places Asia in a unique position-as a potential source of novel parasites and diseases to other parts of the globe, as well as a venue to study those parasites and diseases that have spread to the reaches of our planet in their native Asian honey bee hosts. Our knowledge of the coevolutionary arms race between Asian honey bees and their native parasites is sparse. Future efforts should be directed towards filling important gaps in our fundamental knowledge of honey bee defenses so that novel, sustainable management strategies can be developed.